MicroRNA-197 regulates chondrocyte proliferation, migration, and inflammation in pathogenesis of osteoarthritis by targeting EIF4G2 - Gao, Shijie (Biosci Rep, 2020)
Recent studies have demonstrated that microRNAs (miRNAs) are involved in many pathological conditions including osteoarthritis (OA). In the present study, we aimed to investigate the role of miR-197 in OA and the potential molecular mechanism. The expression levels of miR-197 were detected by quantitative real-time PCR analysis. Cell proliferation and migration abilities were performed by 3-(4,5-dimethylthiazol-2-yl)-2,5-di-phenyltetrazolium bromide and transwell assays. The concentrations of inflammatory cytokines, including IL-1β, IL-6, and TNF-α, were detect using ELISA assay. Furthermore, luciferase reporter and rescue assays were applied to identify the functional target gene of miR-197 in OA. The results showed that miR-197 expression was significantly down-regulated in the OA cartilage tissues compared with normal cartilage tissues, accompanied by up-regulation of EIF4G2 expression. An inverse correlation was found between EIF4G2 and miR-197 expressions in OA cartilage tissues. Treatment with miR-197 mimics promoted the growth and migration abilities of chondrocytes, while miR-197 inhibitors induced the opposite effects. Furthermore, restoration of miR-197 significantly decreased IL-1β, IL-6, and TNF-α expression, whereas knockdown of miR-197 led to a induction in these inflammatory mediators. Moreover, EIF4G2 was predicted and confirmed as a directly target of miR-197. Overexpressed miR-197 could down-regulate EIF4G2 expression in chondrocytes, while miR-197 knockdown could elevate EIF4G2 expression. Additionally, EIF4G2 overexpression reversed the effects of miR-197 mimics on chondrocytes proliferation, migration, and inflammation. Taken together, our study demonstrated that miR-197 promotes chondrocyte proliferation, increases migration, and inhibits inflammation in the pathogenesis of OA by targeting EIF4G2, indicating the potential therapeutic targets of the miR-197/EIF4G2 axis for OA treatment.